Examining the Effects of Empowerment on Intellectually Disabled Females in Al-Jouf Region, Saudi Arabia - Alanazi, Adel (Journal of Intellectual Disability - Diagnosis and Treatment, 2022)
Background: Females’ empowerment is prominent in ascertaining economic growth and development. Concerning intellectually disabled females, the impotent charges are because they often face discrimination in education, the workplace, and society and become victims of abuse, neglect, and sexual violence. However, despite being a crucial topic of social interest, the studies in this specific field are limited, especially in Saudi Arabia. Aim of the Study: The present research has examined the effects of empowerment on intellectually disabled females in Saudi Arabia. Method: The research employed semi-structured interviews with 18 respondents, including four education workers, social development workers, and intellectually disabled females. The interview responses have been further analysed and evaluated with the help of thematic analyses. Results and Conclusion: The findings suggest an increased need to empower females in Saudi for poverty reduction, increased literacy rates, ensure educated and socially responsible citizens, happier families, and a violence-free society. Intellectually disabled females are often neglected, abandoned, and sexually ally harassed. Hence, it is essential to empower such females to protect themselves from discrimination and exercise human rights, laws, and policies equally. The results indicate that empowering intellectually disabled females positively affects society by decreasing violence, addressing poverty, and building a healthier, socially responsible, and educated future. Hence, the Saudi government should make disability inclusion for organisations a priority.